Public health in community pharmacy: A systematic review of pharmacist and consumer views - Ferguson Jill S; Eades Claire E; O'Carroll Ronan E (BMC, 2011)
Abstract Background The increasing involvement of pharmacists in public health will require changes in the behaviour of both pharmacists and the general public. A great deal of research has shown that attitudes and beliefs are important determinants of behaviour. This review aims to examine the beliefs and attitudes of pharmacists and consumers towards pharmaceutical public health in order to inform how best to support and improve this service. Methods Five electronic databases were searched for articles published in English between 2001 and 2010. Titles and abstracts were screened by one researcher according to the inclusion criteria. Papers were included if they assessed pharmacy staff or consumer attitudes towards pharmaceutical public health. Full papers identified for inclusion were assessed by a second researcher and data were extracted by one researcher. Results From the 5628 papers identified, 63 studies in 67 papers were included. Pharmacy staff: Most pharmacists viewed public health services as important and part of their role but secondary to medicine related roles. Pharmacists' confidence in providing public health services was on the whole average to low. Time was consistently identified as a barrier to providing public health services. Lack of an adequate counselling space, lack of demand and expectation of a negative reaction from customers were also reported by some pharmacists as barriers. A need for further training was identified in relation to a number of public health services. Consumers: Most pharmacy users had never been offered public health services by their pharmacist and did not expect to be offered. Consumers viewed pharmacists as appropriate providers of public health advice but had mixed views on the pharmacists' ability to do this. Satisfaction was found to be high in those that had experienced pharmaceutical public health Conclusions There has been little change in customer and pharmacist attitudes since reviews conducted nearly 10 years previously. In order to improve the public health services provided in community pharmacy, training must aim to increase pharmacists' confidence in providing these services. Confident, well trained pharmacists should be able to offer public health service more proactively which is likely to have a positive impact on customer attitudes and health.